2021
DOI: 10.1080/15548627.2021.1965712
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic degradation of CCN2 (cellular communication network factor 2) causes cardiotoxicity of sunitinib

Abstract: Excessive macroautophagy/autophagy is one of the causes of cardiomyocyte death induced by cardiovascular diseases or cancer therapy, yet the underlying mechanism remains unknown. We and other groups previously reported that autophagy might contribute to cardiomyocyte death caused by sunitinib, a tumor angiogenesis inhibitor that is widely used in clinic, which may help to understand the mechanism of autophagy-induced cardiomyocyte death. Here, we found that sunitinib-induced autophagy leads to apoptosis of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 98 publications
(114 reference statements)
2
13
0
Order By: Relevance
“…Li et al (2022) found that magnesium isoglycyrrhizinate exerts therapeutic effects on crizotinibinduced hepatotoxicity by decreasing the level of ROS. Xu et al (2022) also reported that GA significantly mitigated Sunitinibinduced cardiotoxicity. We have proved previously that GA could alleviate liver damage through upregulating Nrf2, defensing oxidative stress and inhibiting apoptosis (Cao et al, 2016;Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Li et al (2022) found that magnesium isoglycyrrhizinate exerts therapeutic effects on crizotinibinduced hepatotoxicity by decreasing the level of ROS. Xu et al (2022) also reported that GA significantly mitigated Sunitinibinduced cardiotoxicity. We have proved previously that GA could alleviate liver damage through upregulating Nrf2, defensing oxidative stress and inhibiting apoptosis (Cao et al, 2016;Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Recently, CCN family has been reported to be closely related to autophagy 16,26,27 . In addition, autophagy was reported to be regulated by ERK signaling 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, CCN family has been reported to be closely related to autophagy. 16,26,27 In addition, autophagy was reported to be regulated by ERK signaling. 28 To probe the signaling downstream events of CCN1-mediated osteogenesis, we investigated the effect of CCN1 on autophagy.…”
Section: Ccn1 Induces Autophagy Via Erk Signaling To Promote Osteogen...mentioning
confidence: 99%
“…Although most studies showed that autophagy has a protective effect on neurons, but the existence of autophagic cell death (ACD) indicated that cell death is also executed through autophagy, such as an increase in autophagic flow and autophagic markers is found in dying cells, and inhibition of autophagy by pharmacological inhibitors or genetic methods can also rescue and prevent cell death (Shen et al, 2011;Hensley and Harris-White, 2015). In a variety of disease models, the damage to target organs by pathogenic factors has been further mitigated by pharmacological attenuation of autophagy levels (Li et al, 2017;Xu et al, 2022). LDH and apoptosis assays have been used in several studies to measure the extent of cell damage (Kumar et al, 2018;Zhang et al, 2020), as previously described, neurons cultured in leucine-deficient 10.3389/fncel.2022.1060712 medium showed a significant increase in cellular LDH release and apoptosis, and after administration of autophagy inhibitors, cellular LDH release and apoptosis decreased significantly, suggesting that leucine deficiency induces excessive autophagy in neurons and then causes damage.…”
Section: Discussionmentioning
confidence: 99%